Stress Analysis of Guide Rails of Elevators - Shuka, Hayder Al-; Wajidi Wisam ِ Al- (Al-Khwarizmi Engineering Journal, 2009)
The mechanical design of elevator elements is always performed by international standards. The engineer selects the appropriate elements of elevator according to catalogues without knowing scientific details. Therefore, a theoretical analysis is achieved at two operating conditions for guide rails (1) safety gear operation, and (2) running condition with the loads unevenly distributed on the elevator car. The guide rail is considered a continuous beam with variable supports. Then the British code is listed showing the equations used in it. The theoretical equations showed that guide rails are never subjected to stress in simultaneous combined buckling and bending in the plane, where the bending moment is exerted. It is always a combination of pressure and bending. Consequently, it is wrong to consider a simultaneous effect of buckling and bending. The equations in the catalogues oppose the theoretical results concerning buckling of guide rails. Therefore, a recommended calculation method for guide rails is presented to be an acceptable method for analysis of guide rail.